Ukrajina: Co ukázaly první čtyři týdny Putinovy třídenní války - Pešek, Jiří; Lohmann, Nina (Lidé města, 2022)
Russia’s invasion of Ukraine in 2022 confronts a peaceful Europe with a shocking war that respects neither the established order nor international law and conventions. Ukraine has surprised the world with its heroic and effective defence. Russian President Putin’s plan to quickly and easily conquer a smaller neighbouring country has effectively failed, and his army has suffered huge losses. This essay analyses the major features of the first month of the war, the painful “awakening” of the Western democratic community of states, the preconditions for a successful Ukrainian defence, and the reasons for Russia’s failure. The second part of the text examines the looming, unexpectedly large and complex global implications of Russia’s “special operation” in Ukraine. The negative consequences of Russia’s brutal aggression for Ukraine, Europe, Africa, and the Middle East are enormous. The ways to address them have not yet even begun to be seriously discussed.